Pengaruh Latihan Flick Bola Diam dan Latihan Flick Bola Bargerak terhadap Hasil Tembakan Hoki - Septianingrum, Kartika; Rahayu, Setya (Media Ilmu Keolahragaan Indonesia, 2014)
The purpose of this study was to determine the effect from flick exercise and drag flick exercise, and to determine witch one more better to shoot in beginner player. This study uses quantitative research using experimental design approach pre test and pos test. Analysis use t test. The result by the everage in eksperiment 1 group are 24,17 and after exercise increaws are 16,67 so value after exercise are 40,83, so there are effect flick and drag flick exercise to shoot in beginner player. The result by the everage in eksperiment 2 group are 22,50 and after exercise increaws are 23,33 so the value after exercise are 45,83. So there are effect drag flick and flick exercise to shoot in beginner player. Witch one more better between exercise start from flick and drag flick can see the average post test flrom eksperiment 1 and 2, 40,83<45,83 and progress from exercise 16,67<23,33. Conclusion of this study are drag flick and flick exercise more better than flick and drag flick exercise to shoot in amatir player. Given the limited ability, time, effort and the results of this study, should be followed up with a related or similar research.